Entwicklung der transaltorischen Kompetenz im rahmen des Postgraduierten Studiums für Übersetzer und Dolmetscher am institut für germanistik an der Universität Wrocław - Małgorzewicz, Anna (Glottodidactica, 2008)
The article presents the didactic concept of the teaching done during the postgraduate course for translators. The author describes the theoretical basis of the translation model, which was the point of departure for the teaching methodology design. The teaching aims are formulated and the concept of translational competence is defined. The author concentrates mainly on the development of interpreting skills. She also presents the typology of activities which develop these skills.